Neuroprotective Effect of Low Mean Arterial Pressure on Postoperative Cognitive Deficit Attenuated by Prolonged Coronary Artery Bypass Time: A Meta-Analysis - Farshad Hasanzadeh Kiabi; Aria Soleimani; Mohammad Reza Habibi (Brazilian Journal of Cardiovascular Surgery)
Abstract Introduction: The true influence of the low mean arterial pressure (low MAP) during coronary artery bypass grafting (CABG) on the development of postoperative cognitive deficit (POCD) remains controversial. We aimed to perform a meta-analysis and meta-regression to determine the effect of low MAP on POCD, as well as moderator variables between low MAP and POCD. Methods: The Web of Science, PubMed database, Scopus and the Cochrane Library database (up to June 2018) were searched and retrieved articles systematically reviewed. Only randomized controlled trials (RCTs) comparing maintenance of low MAP (<80 mmHg) and high MAP (>80 mmHg) during cardiopulmonary bypass (CPB) were included in our final review. Statistical analysis of the risk ratio (RR) and corresponding 95% confidence interval (CI) was used to report the overall effect. The overall effect and meta-regression analysis were done using Mantel-Haenszel risk ratio (MHRR) and the corresponding 95% confidence interval (CI). Results: A total of 731 patients in three RCTs were included in this study. POCD occurred in 6.4% of all cases. Maintenance of low MAP did not reduce the occurrence of POCD (MHRR 1.012 [95% CI 0.277-3.688]; Z=0.018; P=0.986; I2=66%). Shorter CPB time reduced the occurrence of POCD regardless of group assignment (MH log risk ratio -0.519 [95% CI -0.949 - -0.089]; Z= -2.367; P=0.017). Conclusion: POCD is a common event among CABG patients. The neuroprotective effect of low MAP on POCD was attenuated by the prolonged CPB time.